Chinese Scholars on the Progress and Outcomes of the Military Reforms in Russia (from the 1990s till Present) - Shiying Han (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Since the early 1990s, Russia and China have come a long way in developing military cooperation. It began with an exchange of delegations, the reduction of troops along the border, the adoption of confidence-building measures, and, by now, has transformed into a strong partnership. Two countries annually conduct several joint military exercises and develop military training cooperation. In this regard, the Chinese assessments of the Russian military policy after the collapse of the USSR are of particular interest. The survey of specialized publications shows that Chinese scholars commenced studies on the Russian military reforms in the mid-1990s. The author notes that there was a spike of research activity on that matter in 2009 soon after the start of radical reforms of the Russian Armed Forces. Chinese scholars usually identify four waves in the Russian military reforms, each determined by a combination of domestic and external political and economic factors. Chinese military and academic experts assessed these reforms both in terms of their impact on the global balance of power in the military-political sphere and their potential relevance to similar reforms in China. The first two phases of the Russian military reforms (from 1992 to 1997 and from 1997 to 1999) are usually assessed negatively. The general failure of military reforms is attributed to the economic challenges, the lack of political will, and the absence of an adequate theoretical and methodological basis for such transformations. Subsequent reforms (from 2001 to 2004, and, particularly, after 2008) are generally assessed positively. In that regard, Chinese experts emphasize the importance of the processes of political power consolidation and economic recovery that took place in Russia in that period, as well as the role of lessons learned by the Russian military from local wars and armed conflicts. Nevertheless, according to Chinese assessments these reforms still have certain drawbacks, particularly, associated with hasty and misguided attempts to copy the Western military models at the turn of the 2000s — 2010s. In general, Chinese civilian and military experts conclude that throughout a long and difficult process of military reforms Russia has made a significant progress in rearmament and increasing the combat potential of its armed forces. Moreover, such reforms could serve as a valuable source of experience and an example for further development and modernization of the People’s Liberation Army of China (PLA).